Effect of vitamin D vaginal suppository on sexual functioning among postmenopausal women: A three-arm randomized controlled clinical trial - Sarebani, Zinat; Chegini, Venus; Chen, Hui; Aali, Ehsan; Mirzadeh, Monirsadat; Abbaspour, Mohammadreza; Griffiths, Mark D; Alimoradi, Zainab (Obstetrics & gynecology science, 2023)
Vaginal atrophy, the second most common complication of menopause, can lead to sexual dysfunction. This study evaluated the effect of a vitamin D vaginal suppository on sexual functioning in postmenopausal women. This three-arm randomized controlled trial was conducted between August 2019 and August 2020. The sample comprised 105 postmenopausal women who were referred to comprehensive health service centers to receive postmenopausal care. The inclusion criteria were as follows: (i) being menopausal for at least 1 year, (ii) being married, (iii) being sexually active, and (iv) having sexual desire. Participants were randomly assigned to three groups for 8 weeks of treatment: intervention (vaginal suppository containing 1,000 units of vitamin D3), placebo (vaginal suppository placebo), or control (no treatment). The main outcome measure was sexual functioning, which was assessed using the Female Sexual Function Scale (FSFI) 4 times during the study (i.e., 1 month before the intervention, immediately after the intervention, 1 month after the intervention, and 2 months after the intervention). Immediately and 1 month after the trial, the intervention group had the highest FSFI score, followed by the placebo group, both of which were significantly higher than those of the control group (P<0.05). At the 2-month follow-up, the intervention and placebo groups had similar FSFI scores (P=0.08), both of which were significantly higher than those in the control group (P=0.001 and P=0.03, respectively). Vitamin D vaginal suppositories were more effective at improving sexual functioning among postmenopausal women in the short-term and appeared to prevent aging-related sexual functioning decline in the long term.